ANALISIS ASPEK KEPRIBADIAN TOKOH UTAMA DALAM CERPEN-CERPEN KOMPAS.ID TAHUN 2025 (TINJAUAN PSIKOANALISIS SIGMUND FREUD) - Dian Fitri Ramadhani; Een Nurhasanah; Ferina Meliasanti (PENTAS : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2026)
The purpose of this research is to describe the personalities of the main characters in short stories published on Kompas.id in 2025. The data sources for this research consist of five short stories: “Hujan” by Tri Utari, “Pengorbanan Sulung” by Bagus Sulistio, “Bu, Aku Gagal” by Dedy Tri Riyadi, “Rumah di dalam Kepala” by Novand Subyanto Maxsonara, and “Kawah Gunung dalam Dada” by Rahayu Ditira Jayanti, which will be analyzed using a literary psychology approach based on Sigmund Freud’s psychoanalytic theory. This is a qualitative research employing a descriptive-analytical method. Data collection was conducted using documentation and observation-note-taking techniques. The results of this research indicate that (1) Id aspect is evident in basic affective needs, such as the need for affection, emotional comfort, and personal ambition. (2) Ego aspect acts as a mediator, evident through the character’s ability to respond to reality, such as resistance, emotional regulation, and adaptation through hard work. (3) Super Ego aspect is evident through developing moral awareness, manifested in the form of remorse, acceptance, and relationship reconciliation.